1983
DOI: 10.1111/j.1476-5381.1983.tb10018.x
|View full text |Cite
|
Sign up to set email alerts
|

Depolarizing responses to glycine, β‐alanine and muscimol in isolated optic nerve and cuneate nucleus

Abstract: 1Concentration-dependent depolarizations were evoked by glycine and P-alanine 5 x 10-4 -10-2M and by the y-aminobutyric acid (GABA) analogue, muscimol 10-6 -10O4M. 2 The maximal response to glycine was several-fold higher than that to muscimol on optic nerve but the reverse was found on the dorsal funiculus fibres in the cuneate nucleus. P-Alanine evoked a similar maximal response to glycine on optic nerve but a considerably higher maximum than glycine in the cuneate nucleus. 3 Strychnine was 19.5 times more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 15 publications
3
25
3
Order By: Relevance
“…Indeed, several electrophysiological studies showed that clinical concentrations of halothane and enflurane potentiate the glycine-induced Cl-currents in dissociated neurones from the nucleus tractus solitarius of the rat (Wakamori et al, 1991). In addition, Harrison et al (1993) (Machu & Harris, 1994 (Simmonds, 1983). In our study, etomidate and ketamine were completely ineffective on glycine receptor function, while alphaxalone and pentobarbitone produced a modest potentiation of homomeric al glycine receptor function.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, several electrophysiological studies showed that clinical concentrations of halothane and enflurane potentiate the glycine-induced Cl-currents in dissociated neurones from the nucleus tractus solitarius of the rat (Wakamori et al, 1991). In addition, Harrison et al (1993) (Machu & Harris, 1994 (Simmonds, 1983). In our study, etomidate and ketamine were completely ineffective on glycine receptor function, while alphaxalone and pentobarbitone produced a modest potentiation of homomeric al glycine receptor function.…”
Section: Discussionmentioning
confidence: 56%
“…For instance, glycine could inhibit inhibitory interneurones in the striatum; inhibit inhibitory heteroreceptors on dopaminergic terminals; de-inactivate local calcium channels by membrane hypopolarization (Llinas et al, 1983); or increase transmembrane Cl-conductance in nearby axons (Simmonds, 1983;Raiteri et al, 1990), thereby producing receptor-mediated depolarization rather than hyperpolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal optic nerve nicotinic acetylcholine receptor (nAChR) activation has a similar effect upon action potential conduction (Zhang et al, 2004), and the actions of both GABA-A and nAChR activation are largely reversible. β-Adrenoreceptor or serotonin receptor activation also reversibly effects axon excitability in this preparation (Honmou and Young 1995;Saruhashi et al, 1997), while glycine receptor activation has a powerful depolarizing effect upon the membrane potential of neonatal optic nerve axons (Simmonds 1983). The significance of the expression of neurotransmitter receptors other than those for glutamate in developing central white matter for injury has not been examined and previous studies have concentrated upon brief periods of receptor activation.…”
Section: Introductionmentioning
confidence: 99%